Improving Community Digital Literacy Capability in Efforts to Build a Digital Village - Amil Ahmad Ilham; Zahir Zainuddin; Ingrid Nurtanio; Indra Bayu; Muhammad Nizwar; Adnan Adnan; Elly Warni; Zulkifli Tahir; Ais Prayogi Alimuddin; Christoforus Yohannes; Ady Wahyudi Paundu; Mukarramah Yusuf; Anugrayani Bustamin; Iqra Aswad; Muhammad Alief Fahdal Imran Oemar; Intan Sari Areni; Zaenab Muslimin (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
Digital village is a government program concern on village development to improve the quality of life of rural communities through the use of technology in various aspects of village development. This community service aims to provide essential insight and knowledge regarding Digital Village and its application to support the realization of a smart village. This activity was carried out in Desa Tamaona, Bulukumba Regency, through a socialization process attended by four village officials and ten productive people from the local village. Digital information about this village is still relatively minimal on the Internet, while the potential for natural wealth and products in the village is excellent. Therefore, this activity was carried out to support the concept of village digitization as well as an event to introduce the potential of Desa Tamaona to the outside community. The implementation of this service is carried out by socializing village information applications/systems using the Participatory Rural Appraisal (PRA) method. The results of the initial data collection show that the Desa Tamaona community has sufficient potential for developing a digital village, which is seen from the already high intensity of internet use by the community. After the socialization and training on using the website information system, the participants acknowledged that they got a lot of convenience in accessing information digitally compared to before this activity was carried out. This stage is a motivation for further developing technological resources to achieve the smart village concept, which can also increase digital literacy for the Desa Tamaona community.